2000
DOI: 10.1002/(sici)1521-3927(20000501)21:8<464::aid-marc464>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

A new class of biodegradable hydrogels stereocomplexed by enantiomeric oligo(lactide) side chains of poly(HEMA‐ g ‐OLA)s

Abstract: Two enantiomeric amphiphilic graft copolymers consisting of water soluble poly(2‐hydroxyethyl methacrylate) (HEMA) and biodegradable oligo(L‐lactide) (OLLA) or oligo(D‐lactide) (ODLA) were synthesized by free radical copolymerization. HEMA‐OL(D)LA macromonomers were synthesized by ring opening polymerization of L‐ or D‐lactide. Both HEMA‐OLA macromonomers and graft copolymers were characterized by NMR spectroscopy and gel permeation chromatography. Graft copolymers and their stereocomplexes were analyzed by wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
67
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 18 publications
2
67
0
Order By: Relevance
“…Attaching the poly-HEMA to oligo- d -lactide to form a gel phase of the poly-HEMA without using lethal chemicals, have also been reported. [80] …”
Section: Injectable Hydrogelsmentioning
confidence: 99%
“…Attaching the poly-HEMA to oligo- d -lactide to form a gel phase of the poly-HEMA without using lethal chemicals, have also been reported. [80] …”
Section: Injectable Hydrogelsmentioning
confidence: 99%
“…[38][39][40][41][42][43] Hennink and co-workers reported stereocomplex hydrogels of PLLA-and PDLAgrafted dextrans. [39] Feijen and co-workers reported that PEG-PLA star diblock copolymers, PEG-(PDLA) 8 and PEG-(PDLA) 8 , form stereocomplex hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…[25,26] Blends of poly(LLA) and poly(DLA) form a stereo-complex with a melting point of approximately 230 8C. [27] Stereo-complex formation between poly(LLA) and poly(DLA) has been used to prepare physically cross-linked biodegradable hydrogels, [28][29][30] scaffolds for tissue engineering [31,32] and carriers for drug delivery. [33,34] In this paper we report on the preparation of physically cross-linked TMC-based TPEs.…”
Section: Introductionmentioning
confidence: 99%